Cardiopulmonary Resuscitation in the Neurosurgical Patient under Anesthesia - Chayanika Kutum; Prashant Lakhe; BC, Anil Kumar; Ghimire, Niraj (Nepal Journal of Neuroscience, 2025)
Cardiac arrest inside the neurosurgical theatre is a grave crisis which can end up in a remarkably high mortality rate. It is an uninvited crisis to both the neurosurgeon and the neuroanesthetist. It has numerous causes and can happen during different kinds of surgeries along with positions. Management of cardiac arrests in neurosurgical patient population is a territory that is not well elucidated. Conventional ALS protocols cannot be straightaway applied in neurosurgical patients at all times. With a good comprehension, practitioners can be better geared up to tackle unfavourable cardiac emergencies which can be gruelling to the whole neurosurgical team.